Rural restructuring and conflicting definitions of the rural (problem) in East Germany. - Laschewski, Lutz (My University, 2014)
"Rurality" or "rural life" has not mattered much as a concept in public and political as well as scientific discourses during the 1990s. In recent years, it has experienced a remarkable resurgence. This paper tries to investigate this phenomenon. Therefore, major trajectories of rural change in East Germany since 1989 are briefly described, and rural discourses in selected policy arenas are explored. It is argued that the notion of rurality is differentiated across different discourse arenas. While the notions of rurality are not independent from each other, they do not form a coherent worldview. This fragmentation of rural discourses reflects the increasingly hybrid reconstitution of the global countryside. Paradoxically, the notions of rurality do not reflect this hybridity, but they mostly seem to remain in traditional ways of thinking and largely draw on widespread rural images of village, peasantry, cooperation and natural beauty. The resurgence of rurality in public debates is also an expression of a progressing German integration, in which the East-West divide and the narrative of post-socialist transformation are more and more replaced by new political agendas and new framings of problems and causal relations.
Keywords: Siedlungsstruktur; Regionalstruktur; Theorie; Ländlicher Raum; Raumentwicklung; Regionalentwicklung; Landwirtschaft; Diskurs